1974
DOI: 10.1093/clinchem/20.11.1438
|View full text |Cite
|
Sign up to set email alerts
|

The Hoesch Test: Bedside Screening for Urinary Porphobilinogen in Patients with Suspected Porphyria

Abstract: A little-known procedure for porphobilinogen screening, the Hoesch test, was examined for sensitivity, specificity, and utility as compared to the Watson-Schwartz test. The data demonstrate that its sensitivity is similar to that of the Watson-Schwartz test. The Hoesch test, however, is without false-positive reactions secondary to urobilinogen, and its simplicity makes it easier to use and more easily interpretable. We conclude that the Hoesch test should replace the Watson-Schwartz test for urine porphobilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…Before application of ALA, porphyria was excluded in all patients anamnestically and by the Hoesch test 19. Five hours before laparoscopic surgery was performed, the patients received a sterile, 1% ALA solution (pH 6.5) (Medac, Wedel, Germany), intraperitoneally.…”
Section: Methodsmentioning
confidence: 99%
“…Before application of ALA, porphyria was excluded in all patients anamnestically and by the Hoesch test 19. Five hours before laparoscopic surgery was performed, the patients received a sterile, 1% ALA solution (pH 6.5) (Medac, Wedel, Germany), intraperitoneally.…”
Section: Methodsmentioning
confidence: 99%
“…The withdrawal from the market of the Trace Õ PBG kit by Thermo Scientific has left a gap in the methodology for rapid urinary PBG analysis. Previously widely used qualitative methods such as the Watson-Schwartz test 18 the Rimington method 19 and the Hoesch test 20 are all simple procedures with a lower detection limit of approximately 12 mol/L. However, these methods have been criticized for low sensitivity and poor specificity 21,22 and EQA data from WEQAS showed that at a concentration of 10.7 mol/L (upper reference limit) the percentage assessed as positive was 40% vs. 80% positive using the Trace Õ PBG kit (WEQAS porphyrin guide).…”
Section: Methodsmentioning
confidence: 99%
“…determination and quantification of porphyrins and non-porphyrin precursor patterns in biological samples) are mandatory for an accurate diagnosis, and for starting an appropriate clinical management [3,25,58,[90][91][92]94,95]. According to current knowledge and consensus, an APA is invariably associated with an increased urinary excretion of non-porphyrin precursors [ALA and PBG] [6,25,92,96,97] (Figure 2). For this reason, in case of suspected APA, a fresh light-protected urine sample should be assessed for ALA and PBG concentrations [to date, HPLC assays are the most accurate, but rapid, ion-exchange column tests (column-chromatographic screening tests) are also available] (first-line test) [66,[98][99][100][101][102].…”
Section: The Acute Porphyric Attack: Diagnosis and Differential Diagnmentioning
confidence: 99%